Members of the endocannabinoid system are distinctly regulated in inflammatory bowel disease and colorectal cancer - Grill, Magdalena; Högenauer, Christoph; Blesl, Andreas; Haybaeck, Johannes; Golob-Schwarzl, Nicole; Ferreirós, Nerea; Thomas, Dominique; Gurke, Robert; Trötzmüller, Martin; Köfeler, Harald C.; Gallé, Birgit; Schicho, Rudolf (Scientific reports, 2019)
Preclinical studies have demonstrated that the endocannabinoid system (ECS) plays an important role in the protection against intestinal inflammation and colorectal cancer (CRC); however, human data are scarce. We determined members of the ECS and related components of the ‘endocannabinoidome’ in patients with inflammatory bowel disease (IBD) and CRC, and compared them to control subjects. Anandamide (AEA) and oleoylethanolamide (OEA) were increased in plasma of ulcerative colitis (UC) and Crohn’s disease (CD) patients while 2-arachidonoylglycerol (2-AG) was elevated in patients with CD, but not UC. 2-AG, but not AEA, PEA and OEA, was elevated in CRC patients. Lysophosphatidylinositol (LPI) 18:0 showed higher levels in patients with IBD than in control subjects whereas LPI 20:4 was elevated in both CRC and IBD. Gene expression in intestinal mucosal biopsies revealed different profiles in CD and UC. CD, but not UC patients, showed increased gene expression for the 2-AG synthesizing enzyme diacylglycerol lipase alpha. Transcripts of CNR1 and GPR119 were predominantly decreased in CD. Our data show altered plasma levels of endocannabinoids and endocannabinoid-like lipids in IBD and CRC and distinct transcript profiles in UC and CD. We also report alterations for less known components in intestinal inflammation, such as GPR119, OEA and LPI.